“Going vaccine hunting”: Multilevel influences on COVID-19 vaccination among racialized sexual and gender minority adults—a qualitative study - Peter A. Newman; Duy Anh Dinh; Notisha Massaquoi; Charmaine C. Williams; Ashley Lacombe-Duncan; Suchon Tepjan; Thabani Nyoni (Human Vaccines & Immunotherapeutics, 2024)
ABSTRACTHigh levels of COVID-19 vaccine hesitancy have been reported among Black and Latinx populations, with lower vaccination coverage among racialized versus White sexual and gender minorities. We examined multilevel contexts that influence COVID-19 vaccine uptake, barriers to vaccination, and vaccine hesitancy among predominantly racialized sexual and gender minority individuals. Semi-structured online interviews explored perspectives and experiences around COVID-19 vaccination. Interviews were recorded, transcribed, uploaded into ATLAS.ti, and reviewed using thematic analysis. Among 40 participants (mean age, 29.0 years [SD, 9.6]), all identified as sexual and/or gender minority, 82.5% of whom were racialized. COVID-19 vaccination experiences were dominated by structural barriers: systemic racism, transphobia and homophobia in healthcare and government/public health institutions; limited availability of vaccination/appointments in vulnerable neighborhoods; absence of culturally-tailored and multi-language information; lack of digital/internet access; and prohibitive indirect costs of vaccination. Vaccine hesitancy reflected in uncertainties about a novel vaccine amid conflicting information and institutional mistrust was integrally linked to structural factors. Findings suggest that the uncritical application of “vaccine hesitancy” to unilaterally explain undervaccination among marginalized populations risks conflating structural and institutional barriers with individual-level psychological factors, in effect placing the onus on those most disenfranchised to overcome societal and institutional processes of marginalization. Rather, disaggregating structural determinants of vaccination availability, access, and institutional stigma and mistrust from individual attitudes and decision-making that reflect vaccine hesitancy, may support 1) evidence-informed interventions to mitigate structural barriers in access to vaccination, and 2) culturally-informed approaches to address decisional ambivalence in the context of structural homophobia, transphobia, and racism.